HERMENEUTIKA INTERTEKSTUALITAS MUQÂTIL BIN SULAYMÂN - Rahmatullah, Rahmatullah (UIN Sunan Kalijaga Yogyakarta, 2019)
Intertextuality is one of the contemporary reading theories that discusses texts that cannot be made on their own without relations and relations with other contemporary texts. Intertextuality reading can also be done in reading the Quran. Muqâtil bin Sulaymân is one of the early interpreters who tried to apply intertextuality hermeneutics. The Quran is a continuation of and responds to the scriptures, so he does not hesitate to dialogue with the Quran with the Bible. Most intertextuality hermeneutics built by Muqâtil can be accessed in two aspects. First, the aspects explain things that are not yet clear (mubham), like the names of the characters told in the Quran. Second, the aspect of emphasis is on the historicity and context of the verses of the Quran. This aspect was carried out by Muqâtil by exploring the sources of religion that developed at that time. However, the criticism that needs to be addressed in the method used by Muqâtil is the use of strict non-Islamic history. Muqâtil tends not to notice the process of criticism or materialism in the science of the hadith.